TINJAUAN YURIDIS PEMBERHENTIAN TIDAK HORMAT APARATUR SIPIL NEGARA KARENA MELAKUKAN PIDANA KORUPSI: Juridical Review Disrespectful Dismissal of State Civil Apparatus for Committing Corruption Crimes - Putra, Rivi Pratama; Yurikosari, Andari (Faculty of Law, Universitas Trisakti, 2024)
Every State Civil Apparatus (ASN) has an obligation to always be able to comply with all codes of ethics and regulations that govern, namely the Laws. The Disrespectful Dismissal Case committed by Daduk Agustyanta, Daduk Agustyanta's brother is a Civil Servant (PNS). The formulation of the problem in the case of Daduk Agustyanta's brother is whether the dismissal process does not respect the State Civil Apparatus based on decision Number 24/G/2021/PTUN.Sby in accordance with BKN Regulation Number 3 of 2020 concerning Technical Instructions for Dismissal of Civil Servants and what are the legal consequences for State Civil Apparatuses that are proven commit acts of corruption. Secondary and primary data are used as research supporting data, and normative law is used for descriptive research methods. using qualitative analysis and making conclusions with deductive logic. The results of the study showed that Daduk Agustyanta's brother had been dishonorably discharged based on Law Number 5 of 2014 concerning the State Civil Apparatus. Based on the discussion, the law has binding legal force because it is in accordance with the statutory hierarchy. In conclusion, the dismissal process handed down to brother Daduk Agustyanta was in accordance with the flow of dismissal stipulated in Law Number 5 of 2014 concerning State Civil Apparatuses and the legal consequences received by brother Daduk Agustyanta for committing a Corruption Crime, namely being dishonorably discharged and brother Daduk Agustyanta lost his employment rights and pension rights